Determinants of campus political participation: a case study of AM, AC, and AT faculties at UiTM Sabah, Malaysia. - Ahmad Raud, Afiq Daniel; Markus, Muhammad Asyari; Abbdullah, Nurfaizah; Perman, Azwan Ahzran (Faculty of Administrative Science and Policy Studies, 2025)
In recent years, students' involvement in campus politics is not exhilarating compared to the early 1970s, when politics on campus started to arise. Participation in campus politics is not only focusing on campus elections but also on activism and debate, as well as discussion. This activity has a significant contribution for the future of democracy in Malaysia among the young generation. It is crucial to address these issues with the university students to ensure significant actions could be taken to encourage their participation and to prevent their existence in politics from lessening. Therefore, the researchers believe that there are several factors that are associated with students' participation in campus politics. In this quantitative exploratory study, descriptive analysis was used to determine the mean for the variables. Furthermore, inferential analysis using Kruskal-Wallis and Spearman were observed. The findings highlighted a significant difference in students’ participation in campus politics between the Faculty of Administrative Science and Policy Studies (AM), the Faculty of Accountancy (AC), and the Faculty of Plantation and Agrotechnology (AT). On top of that, the factor of social media has a weak to moderate positive correlation among the three factors studied.